Reappraisal of the Etiology of Extracorpuscular Non-Autoimmune Acquired Hemolytic Anemia in 2657 Hospitalized Patients with Non-Neoplastic Disease - Victor C. Kok; Chien-Kuan Lee; Jorng-Tzong Horng; Che-Chen Lin; Fung-Chang Sung (SAGE Publishing, 2014)
Introduction Unlike autoimmune hemolytic anemia (AIHA), literature on the etiological study of non-autoimmune hemolytic anemia (non-AIHA) is scarce. The incidence and prevalence of non-AIHA in different geographic regions are largely unknown perhaps owing to the lack of perspective investigation and different profiles of etiologies from different geographic regions. We aimed to examine the real-world etiology or mechanisms of the non-hereditary non-AIHA from a nationwide population-based administrative claim database in Taiwan. Patients and Methods The National Health Insurance Research Database of Taiwan was adopted for this research. The studied population was total inpatient claim records including both pediatric and adult patients, contributed by a population of 23 million insured individuals in Taiwan. From 2002 to 2008, we retrieved 3,903 patients having no pre-existing malignancy discharged after inpatient management for acquired hemolytic anemia, which was defined as coding in discharge diagnoses containing ICD-9-CM code 283. By contrast, ICD-9-CM code 282 and all of the sub-codes are for hereditary hemolytic anemias. Results AIHA accounted for 32% of the total cases. Among 2,657 patients with non-AIHA, mechanical or microangiopathic mechanism accounted for 19% of cases; hemolytic-uremic syndrome (HUS) 4%, hemoglobinuria because of hemolysis from external causes such as paroxysmal nocturnal hemoglobinuria (PNH) and march hemoglobinuria 7%, and chronic idiopathic hemolytic anemia or other unspecified non-AIHA 69%. We looked further for specific etiology or mechanism for this group of patients with non-hereditary extrinsic non-AIHA (n = 2,657). The explanatory disease states or conditions were splenomegaly; alcohol use disorder (spur cell hemolysis); heart-valve prosthesis; malignant hypertension; disseminated intravascular coagulation; transfusion reaction; dengue fever-induced hemolytic anemia; direct parasitization; snake, lizard, or spider bite; and Wilson's disease with internal toxin mechanism. All these cases can explain up to 34.6% of all the non-hereditary extrinsic non-AIHA cases. Fragmentation hemolysis (HUS, heart-valve prosthesis, malignant hypertension, and disseminated intravascular coagulation) accounted for 7.4% of non-AIHA hospitalized patients with non-neoplastic disease. Conclusions This article is the first one to clearly demonstrate that the non-neoplastic-induced HUS requiring hospitalization cases in Taiwan, which has a population of over 23 million were 110 over a span of seven years, 16 cases per year. Although the etiologies of non-AIHA are well known and described in the literature, this work added the statistical percentages of the various etiologies of non-AIHA in Taiwan.